2003
DOI: 10.1001/archneur.60.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Early Clinical Severity and Extent of Neuronal Damage in Anterior-Circulation Infarction Using the Initial Serum Neuron-Specific Enolase Level

Abstract: The initial serum NSE level is a reliable predictor for the extent of neuronal damage and the severity of clinical neurological deficits in acute anterior-circulation infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 33 publications
3
48
1
1
Order By: Relevance
“…Best correlations with infarct volume were found for the 2-to-4-day interval after stroke. 12,17 In this time interval, we found an association between S100␤ concentrations and the presence and volume of postoperative DWI lesion. However, on the level of single measurements (Figure 4), we doubt the clinical usefulness of this parameter for identifying patients with perioperative embolic brain lesions because the lesion volume in these patients is generally small and the power of S100␤ to separate groups with or without postoperative DWI lesions is weak.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Best correlations with infarct volume were found for the 2-to-4-day interval after stroke. 12,17 In this time interval, we found an association between S100␤ concentrations and the presence and volume of postoperative DWI lesion. However, on the level of single measurements (Figure 4), we doubt the clinical usefulness of this parameter for identifying patients with perioperative embolic brain lesions because the lesion volume in these patients is generally small and the power of S100␤ to separate groups with or without postoperative DWI lesions is weak.…”
Section: Discussionmentioning
confidence: 57%
“…S100␤ and NSE concentrations have been found to correlate closely with the volume of territorial ischemic stroke. 12,17 However, timing of measurements is crucial. Best correlations with infarct volume were found for the 2-to-4-day interval after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a group of authors also reported high correlation between the serum NSE to the volume of lesion within 24 hours of acute ischemic stroke onset( r=0.62, p<0.001). [7] A group of Indian authors also reported a positive significant correlation between concentration of NSE on day 1 and infarct volume as determined by CT scan in acute ischemic stroke patients(r=0.955, p<0.001). [8] In another study also, a significant positive correlation of serum NSE level to the CT scan volume of lesion( r=+0.993; p<0.001) has been reported in acute ischemic stroke patsients within 24-48 hours of stroke onset.…”
Section: Discussionmentioning
confidence: 97%
“…Thus high levels of NSE in serum/CSF often indicate neuronal damage in case of neurological disorders such as stroke [16]. Some studies have shown a positive correlation between NSE levels and infarct volume in patients of AIS [17,18]. S100 ββ is a calciumbinding protein expressed mainly in human astroglial cells.…”
Section: Discussionmentioning
confidence: 99%